AB0153 Comparative proteomic analysis of neutrophils from patients with microscopic polyangiitis and granulomatosis with polyangiitis. (23rd January 2014) - Uchida, T.; Nagai, K.; Sato, T.; Iizuka, N.; Arito, M.; Takakuwa, Y.; Nakano, H.; Ooka, S.; Kurokawa, M.; Suematu, N.; Okamoto, K.; Ozaki, S.; et al.
Abstract : Background: Both microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA) belong to ANCA-associated vasculitis (AAV), in which neutrophils are thought to be involved in their pathology. Clinically, it is often difficult to distinguish MPA from GPA. To discriminate between MPA and GPA, protein profiles of peripheral blood polymorphonuclear cells (PMNs) of MPA and GPA patients and healthy controls (HC) were analyzed. Objectives: In this study, proteomic profilesof PMN of AAV patients and healthy controls (HC) were analyzed using two-dimensional difference gel electrophoresis (2D-DIGE), in order to confirm whether the profiles are useful to discriminate between AAV and HC, or MPA and GPA. Methods: Proteins extracted from peripheral blood PMNs of 11 MPA patients, 9 GPA patients, and 10 HC were separated by two-dimensional difference gel electrophoresis (2D-DIGE). Differentially expressed protein spots were identified by mass spectrometry analysis. Then, to find biomarker candidates which discriminate between MPA and GPA, the obtained protein profiles were subjected to the multivariate data analysis using SIMCA-P+ containing principal component analysis (PCA) and orthogonal partial-least-squares-discriminate analysis (OPLS-DA), and subjected to the receiver operating characteristic (ROC) analysis. Results: In all the 864 protein spots detected, intensity of 55 spots was found to be significantly different ( p < 0.05) among the three groups by an analysis of variance (ANOVA). 31 out of the 55 spots were identified by mass spectrometry. The OPLS-DA analysis revealed that the expression profile of the protein spots discriminated the AAV group from the HC group completely and also discriminated the MPA group from the GPA group completely. 13 protein spots were considered as biomarker candidates to distinguish between MPA and GPA. In those, spots whose intensity was higher in MPA than in GPA included actin with various p I values, while a considerable part of spots whose intensity was higher in GPA than MPA were proteins related with the activity of neutrophils. Among the candidate proteins, ROC analysis showed that a combination of neutrophil gelatinase-associated lipocalin and a kinase anchor protein 7 isoforms beta had a high diagnostic potential. Conclusions: In the study, we determined that the protein profile of the neutrophil was clearly different between AAV and HC, and between MPA and GPA. In Particular, GPA was characterized by high expression level of the proteins associated with the activity of the neutrophil. Disclosure of Interest: None Declared